Hybrid: Barn Swallow x Common House Martin - Pickles, Andrew (Biodiversity Observations, 2014)
In the hand this particular bird appeared to be more House Martin than Barn Swallow though the measurements fall exactly between those of the two species. In the hand the bird felt substantially smaller than the Barn Swallow.